EXERGETIC PERFORMANCE OF VAPOR-COMPRESSION REFRIGERATION SYSTEM WITH TiO2 NANOADDITIVE IN THE COMPRESSOR OIL - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Vinca Inst Nuclear Sci, 2021)
Exergy analysis of a vapor-compression refrigeration system with TiO2 nanoadditives in the compressor oil was performed. Two-step method was used for the preparation of nanooil for various solid particle volume fractions between 0% and 1%. Irreversibilities were determined by using the Second law of thermodynamics. It is found that a reduction in total irreversibility is achieved with nano-particle inclusion and it was significant for higher particle volume fraction.
Keywords: refrigeration; nanooil; thermodynamic; irreversibility